Adaptive Teaching Strategies of Indonesian Pre-Service Teachers in Teaching English at Thai Schools in Krabi, Thailand - Salsabiila Alifya Khasanah; Suciana Wijirahayu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the adaptive teaching strategies employed by Indonesian pre-service English teachers when teaching English in Thai schools in Krabi, Thailand. Teaching in a multicultural and multilingual EFL context requires teachers to be flexible and responsive to students’ linguistic abilities, cultural backgrounds, and learning needs. This research focuses on how pre-service teachers adapt their instructional strategies, address cultural and pedagogical challenges, and develop professional competence during their teaching internships. This study employed a qualitative multiple-case study design involving ten Indonesian pre-service English teachers from a private university in East Jakarta who joined KKN & Magang Internasional in Krabi, Thailand. Data were collected through semi-structured interviews, classroom observations, and documentation, and analyzed using thematic analysis. The findings indicate that the participants demonstrated readiness to adapt their teaching methods, utilize various instructional media and materials, and integrate cultural awareness into their teaching classroom practices. These adaptive strategies in response to students’ needs, classroom environment, and language proficiency levels, contributed to improved student engagement and the development of intercultural competencelearning effectiveness.